The possibility of application of weather derivatives by agricultural market in Kazakhstan on the expert opinion - Kusniyeva, A.T. (BUKETOV BUSINESS REVIEW, 2019)
In this paper weather derivatives as a possible tool for hedging weather risks are studied. Due to the sharply continental climate of Kazakhstan, the weather has a significant impact on business income, related to weather conditions. This article is focusing on the wheat market, since its export has a large potential for econmic development and diversification of the economy of Kazakhstan. The aim of this article is identification of the necessity of application of the weather derivatives tool among agricultural wheat producers based on expert opinion. In connection with the novelty of the instrument in Kazakhstan at the beginning of the work the concept and mechanism of weather derivatives is explained. Further the relevance of weather risks for Kazakhstani farmers is proved, as well as the specifics of weather conditions for growing quality wheat is revealed. At the moment, Kazakhstani farmers are struggling with weather risks using crop insurance. In spite of the fact that crop insurance does not satisfy local farmers, they are obliged to use this tool on the basis of the Law «On compulsory crop insurance». In this regard, the article provides a comparative analysis of weather derivatives and crop insurance. According to the analysis and farmers’ opinion, weather derivatives are a more ellective tool for hedging of weather risks and have several advantages over insurance. In conclusion, the research methodology and results of interviews on the theme of weather derivatives and general market condition. Based on the work, an obvious interest on the tool of weather derivatives and the need for their implementation in the market of Kazakhstan is revealed.